DOSE OPTIMIZATION ON LIVER CANCER PROTON THERAPY AND BORON NEUTRON CAPTURE THERAPY USING PARTICLE AND HEAVY IONS TRANSPORT CODE SYSTEM - Hafiz Fahrurrozi; Andang Widi Harto; Isman Mulyadi Triatmoko; Gede Sutrisna Wijaya; Yohannes Sardjono (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2021)
Liver cancer was the third leading cause of death from cancer in 2020 with 830,180 deaths worldwide. Radiotherapy is a common treatment method for liver cancer. Technological advances presented proton therapy and boron neutron capture therapy (BNCT) as alternatives with a lower dose on healthy organs. The objective of this research is to get a good dose distribution with higher tumor dose and lower healthy organ dose in proton therapy. A comparison with BNCT is done to get a better understanding of how both methods deliver the dose to treat the cancer while minimizing healthy organ doses. The research simulated proton therapy for cancer liver with Particle and Heavy Ions Transport Code System (PHITS), and a literature review for BNCT. The effectiveness of both methods were compared by tumor dose and liver dose. The optimal tumor dose for proton therapy is 86.01 Gy (W) with 0.67 Gy (W) liver dose. Proton therapy can replace conventional radiotherapy for tumors with complex shapes in dose delivery by utilizing its dose profile, while BNCT can give better tumor control on patients previously treated with conventional radiotherapy.